Effects of Electronic Strategic Intervention Material on Elementary Students’ Motivation in Learning Plant and Animal Cells - Dichoso, Julie Ann H; Reyes, Lance D Delos; Feolino, Ivy; Lasala, Nestor Jr (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aimed to develop and validate a Self-Determination Theory-based Electronic Strategic Intervention Material (E-SIM) designed to enhance students’ intrinsic motivation in learning about plant and animal cells. The E-SIM was anchored on the Department of Education’s Most Essential Learning Competencies (MELCs) to ensure curriculum alignment and contextual relevance. Methodology: A descriptive-developmental design was employed for material validation, and a one-group pretest posttest design (n = 39) was used to evaluate its effectiveness. Data were collected through expert and student validation checklists, as well as the Intrinsic Motivation Inventory (IMI). Quantitative analyses included the Shapiro–Wilk test for normality and the Wilcoxon signed-rank test to determine significant changes in motivation levels. Main Findings: Expert validators rated the E-SIM “Very Satisfactory” in content, instructional, and technical quality, while student evaluators rated it “Excellent” in content and “Very Good” in format. The Wilcoxon signed-rank test revealed a significant increase in intrinsic motivation after E-SIM implementation (p < .05; r = 0.84), particularly in Interest/Enjoyment and Value/Usefulness subscales, alongside a notable decrease in Pressure/Tension. Novelty/Originality of this study: This study introduces a technology-enhanced, game-based E-SIM developed through Microsoft PowerPoint with integrated narration, animations, and interactive feedback mechanisms. Grounded in Self Determination Theory, the E-SIM promotes autonomy, competence, and enjoyment demonstrating its potential as an engaging, low-cost, and scalable alternative to traditional instruction in fostering students’ motivation and learning in biology.